Nilai dan Fungsi Lebaran Ketupat dalam Masyarakat di Desa Gantiwarno Lampung - Nisa, Khairun (Yayasan Alpatih Harapan Semesta, 2025)
Eid Ketupat is a tradition celebrated by people in Indonesia, especially in Java, as a form of thanksgiving after fasting. This tradition usually takes place one week after Eid al-Fitr and involves serving Ketupat, which is rice wrapped in woven coconut leaves. In a social and cultural context, Eid Ketupat has a deep meaning for society, because it is not just a celebration, but also a means of strengthening ties between residents. This tradition is rooted in local cultural values that prioritize togetherness, helping each other and sharing. Every year, people will gather to cook Ketupat and other typical dishes, as well as hold gatherings. Apart from that, Eid Ketupat also functions as a moment of reflection to forgive each other and strengthen social relations within the community. In this research, the author will explore the implementation of the Eid Ketupat tradition in villages, exploring the meaning behind this ritual, as well as the social and cultural functions contained in it. Thus, it is hoped that this journal can provide a deeper understanding of the importance of this tradition in the context of people's lives, as well as its contribution to the preservation of local culture in Indonesia. The research method used is qualitative in descriptive form.